Solid electrolyte

By using solid electrolytes containing garnet-type composite metal oxide phase and specific phase (D) in lithium-ion secondary batteries, using mechanochemical treatment and sintering technology, the insufficient lithium ion conductivity in lithium-ion secondary batteries is solved. The problem of high-performance battery solid electrolyte is realized.

CN115066731BActive Publication Date: 2025-02-07KANEKA CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180012923.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-05
Filing Date
2021-02-02
Publication Date
2025-02-07
Estimated Expiration
2041-02-02

AI Technical Summary

Technical Problem

In the prior art, the solid electrolyte of lithium-ion secondary batteries has shortcomings in terms of safety, long-term cycle stability and energy density, especially the lithium-ion conductivity is not ideal.

Method used

A solid electrolyte containing a garnet-type composite metal oxide phase (L) and a phase (D) different from the phase (L) is used. The aforementioned phase (L) contains Li, La, Zr and O, and the Li site is partially The replaced Ga and phase (D) include phases composed of LiF, BaZrO3, YF3, SrF2 and ScF3, and the Li+ ion conductivity is improved through mechanochemical treatment and sintering technology.

Benefits of technology

Good Li+ ion conductivity is achieved, making it suitable for high-performance solid electrolytes for secondary batteries, improving the safety and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115066731B_ABST
    Figure CN115066731B_ABST
Patent Text Reader

Abstract

The present invention aims to provide a solid electrolyte comprising a garnet-type composite metal oxide phase and exhibiting good lithium ion conductivity. The present invention is a solid electrolyte, characterized in that it comprises a garnet-type composite metal oxide phase (L) and a phase (D) different from the phase (L), wherein the phase (L) comprises Li, La, Zr and O, and Ga that replaces a portion of the Li site, the lattice constant of the solid electrolyte is greater than #imgabs0#, and the phase (D) comprises at least one selected from the group consisting of LiF, BaZrO3, YF3, SrF2 and ScF3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to solid electrolytes. Background Art

[0002] Research and development of Li-ion secondary batteries are actively being conducted for portable devices, hybrid vehicles, electric vehicles, and household power storage applications. Li-ion secondary batteries used in these fields are required to have high safety, long-term cycle stability, high energy density, and the like.

[0003] Among them, all-solid-state batteries using solid electrolytes have attracted attention due to their high safety. For example, the lithium ion conductor LIC of Patent Document 1 is manufactured by first preparing an ion conductor, mixing lithium halide and the ion conductor, and heating. 12 In the case of LLZ-MgSr powder in which Mg and Sr elements have been replaced, the raw materials of each element comprising LLZ-MgSr (Li2CO3, MgO, La(OH)3, SrCO3, ZrO2, SrCO3, ZrO2) are mixed for 15 hours, sintered at 1000°C for 10 hours, and then mixed with lithium halide (e.g. LiI) powder to obtain a mixed powder, which is pressed together with a stainless steel collector using a press to obtain a pressed powder, and heat treated at 80°C for 17 hours.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2017-91788 Summary of the invention

[0007] Problem that the invention aims to solve

[0008] The present invention aims to provide a Li-ion battery comprising a garnet-type composite metal oxide phase and exhibiting good lithium ion conductivity, which is different from that of Patent Document 1. + Ion-conducting solid electrolyte.

[0009] Solutions for solving problems

[0010] The present invention which solves the above-mentioned problems is as follows.

[0011] [1] A solid electrolyte comprising a garnet-type composite metal oxide phase (L) and a phase (D) different from the phase (L),

[0012] The phase (L) contains Li, La, Zr, O, and Ga that is disposed on a portion of the Li site.

[0013] The lattice constant of the solid electrolyte is above,

[0014] The phase (D) includes at least one selected from the group consisting of LiF, BaZrO3, YF3, SrF2 and ScF3.

[0015] [2] The solid electrolyte according to [1], wherein the phase (D) further contains at least one of Al and La when containing LiF.

[0016] [3] The solid electrolyte according to [1] or [2], wherein the phase (D) is present at at least a portion of the interface of the phase (L).

[0017] [4] A solid electrolyte comprising a garnet-type composite metal oxide phase (L),

[0018] The solid electrolyte is a LiX 1 and MX 2 p (X 1 and X 2 All are F, Cl, Br or I, X 1 and X 2 A raw material mixture containing a Li source powder, a La source powder, a Zr source powder and a Ga source powder is mechanochemically treated in the presence of a reaction aid of a mixture of (optionally the same or different, M is Ba, Y, Sr, or Sc, and p is a value equal to the atomic valence of M),

[0019] The phase (L) contains Li, La, Zr, O, and Ga that replaces a part of the Li site.

[0020] [5] The solid electrolyte according to [4], wherein the X 1 and X 2 All are F.

[0021] [6] A solid electrolyte according to [4] or [5], wherein a phase (D) exists at at least a portion of the interface of the aforementioned phase (L), and the phase (D) is a phase of a compound containing at least a portion of the constituent elements of the aforementioned reaction aid and is different from the aforementioned phase (L).

[0022] [7] The solid electrolyte according to any one of [1] to [6], wherein Li + The ionic conductivity is 1.0×10 -4 S / cm or more.

[0023] [8] The solid electrolyte according to any one of [4] to [7], wherein the reaction aid is contained in an amount of 15 parts by mass or less relative to 100 parts by mass of the total raw material mixture.

[0024] [9] The solid electrolyte according to any one of [4] to [8], wherein after the mechanochemical treatment, calcination is performed at 1100 to 1350° C. for 10 to 30 hours.

[0025] Effects of the Invention

[0026] The solid electrolyte of the present invention exhibits good Li + It has high ion conductivity and can therefore be used as a member of an excellent solid electrolyte for secondary batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 middle, Figure 1 (a) is a cross-sectional view perpendicular to the rotation axis of a grinding machine that can be used in the mechanochemical method, Figure 1 (b) is Figure 1 (a) AA' cross-sectional view.

[0028] Figure 2 This is a diagram showing the results of XRD analysis of samples obtained in Production Examples described later.

[0029] Figure 3 This is a diagram showing the results of XRD analysis of samples obtained in Production Examples described later.

[0030] Figure 4 This is a photograph in lieu of a drawing showing a cross-sectional TEM image of a pellet obtained in an example described later.

[0031] Figure 5 This is a photograph in lieu of a drawing showing a cross-sectional TEM image of a pellet obtained in an example described later.

[0032] Figure 6 This is a diagram showing the results of EDS analysis of a cross section of a pellet obtained in an Example described later.

[0033] Figure 7 This is a diagram showing the results of TEM-EDS analysis of a cross section of a pellet obtained in an example described later.

[0034] Figure 8 This is a diagram showing a cross-sectional TEM-EELS image of a pellet obtained in an example described later.

[0035] Fig. 9 This is a diagram showing the results of XRD analysis of samples obtained in the Production Examples and Examples described later.

[0036] Fig.10 This is a diagram showing the results of XRD analysis of samples obtained in the Production Examples and Examples described later.

[0037] Fig.11This is a diagram showing the results of EDS analysis of a cross section of a pellet obtained in an Example described later.

[0038] Fig.12 This is a diagram showing the results of XRD analysis of samples obtained in the Production Examples and Examples described later.

[0039] Fig.13 This is a diagram showing the results of EDS analysis of a cross section of a pellet obtained in an Example described later.

[0040] Fig.14 This is a diagram showing the results of XRD analysis of samples obtained in the Production Examples and Examples described later. DETAILED DESCRIPTION

[0041] The solid electrolyte of the present invention is a solid electrolyte comprising a garnet-type composite metal oxide phase (L) and a phase (D) different from the phase (L), wherein the phase (L) comprises Li, La, Zr and O, and Ga that replaces a portion of the Li site, and the lattice constant of the solid electrolyte is As described above, the phase (D) includes at least one selected from the group consisting of LiF, BaZrO3, YF3, SrF2 and ScF3.

[0042] The garnet-type composite metal oxide phase (L) containing Li, La, Zr and O can be generally composed of Li7La3Zr2O 12 The composition formula is represented by . The aforementioned phase (L) is preferably a cubic crystal. In addition, the aforementioned garnet-type composite metal oxide phase (L) contains Ga that replaces a portion of the Li site. Hereinafter, the garnet-type composite metal oxide is sometimes referred to as "LLZ". In the present invention, LLZ is preferably a cubic crystal.

[0043] The solid electrolyte of the present invention includes, in addition to the aforementioned phase (L), a phase (D) different from the phase (L). Phase (D) includes at least one selected from the group consisting of LiF, BaZrO3, YF3, SrF2 and ScF3. In a preferred embodiment, when the aforementioned phase (D) includes LiF, it also includes at least one of the Al element and the La element. At least one of the Al element and the La element can form an oxide, and as the oxide, Al oxide, La oxide, and a composite oxide of Al and La can be cited. Among them, when the aforementioned phase (D) includes LiF, it preferably includes LiF and La elements, and more preferably includes LiF, La element and Al element. The La element contained in the aforementioned phase (D) is generally derived from the La source powder described later. In addition, the Al element may be, for example, Al contained as an impurity in the raw material powder described later or derived from a crucible.

[0044] The presence of LiF, BaZrO3, YF3, SrF2 and ScF3 can be confirmed based on the results of measurements by EDS (energy dispersive X-ray spectroscopy), XRD (X-ray diffraction), TEM (transmission electron microscopy)-EELS (electron energy-loss spectroscopy), or by appropriately combining these results.

[0045] In addition, the lattice constant of the solid electrolyte of the present invention is In general, the lattice constant of LLZ partially substituted with Ga (hereinafter referred to as Ga-substituted LLZ) is The lattice constant of the solid electrolyte of the present invention is larger than that of the Ga-substituted LLZ. The reason for this is not yet determined, but it is believed that part of the Li site is replaced by an element derived from the reaction aid component. The aforementioned lattice constant is preferably More preferably The above, more preferably The upper limit of the lattice constant is not particularly limited, and can be, for example,

[0046] Usually, the phase (D) is present at least in a portion of the interface of the phase (L). That is, the phases (L) preferably have a region where the phase (D) is sandwiched between each other, and in this region, the phases (L)-phase (D)-phase (L) are in contact with each other in this order. By the presence of the phase (D) at least in a portion of the interface of the phase (L), Li + Ions can be well conducted from phase (L) to phase (L) via phase (D).

[0047] The solid electrolyte of the present invention may be a powder, or a compact (compression molded product) obtained by compression molding the powder, and more preferably a sintered body obtained by sintering the compression molded product. The relative density of the solid electrolyte of the present invention is preferably 60% or more, more preferably 70% or more, further preferably 80% or more, further preferably 90% or more, and the upper limit may be 100%, or about 95%.

[0048] The solid electrolyte of the present invention is obtained by subjecting a mixture of raw material powders to a mechanochemical treatment in the presence of a specified reaction aid, and the raw material powders are reacted with each other during the mechanochemical treatment, thereby producing LLZ. More specifically, the mechanochemical method can be performed by compressing and shearing the mixture of raw material powders under dry conditions, accumulating strain energy in the raw material powders, which is self-released and converted into heat energy, or consumed in surface modification, crystal structure transformation, or solid phase reaction. In the present invention, subjecting the raw material powders to a mechanochemical treatment in the presence of a specified reaction aid can promote the reaction between the raw material powders and increase the Li + Ionic conductivity.

[0049] More specifically, the mechanochemical treatment can be performed by compressing and shearing a mixture containing a raw material powder and a reaction aid under dry conditions. An example of this method will be described using the drawings. Figure 1 This is a schematic diagram of a grinder that can apply compression and shear forces to a mixture of raw material powders and a reaction aid. Figure 1 (a) is a cross-sectional view perpendicular to the rotation axis. Figure 1 (b) is Figure 1 (a) AA' cross-sectional view. Figure 1 The grinding machine has a bottomed cylindrical container 1 and a rotor 2. The rotor 2 has a front blade 3 having a curvature smaller than the inner circumference of the bottomed cylindrical container 1, and a gap 4 is provided between the front blade 3 and the inner circumference of the bottomed cylindrical container 1. When the rotor 2 is rotated, a mixture 5 of a raw material powder and a reaction aid is subjected to a compressive force and a shearing force in the gap 4.

[0050] Regarding the conditions of the mechanochemical treatment, if the reaction conditions are too weak, the raw material powders will not react with each other, and if they are too strong, the temporarily generated LLZ crystals will become amorphous, which is not preferred. When the conditions of the mechanochemical treatment are inappropriate, the conditions can be appropriately changed according to the reasons (unreacted, amorphous, etc.), and according to the type and amount of the raw materials, and the type and amount of the flux, for example, as follows.

[0051] The range of the aforementioned gap varies depending on the amount of raw material powder, the difference between the curvature of the front blade of the rotor and the curvature of the inner circumference of the container, the processing power of the rotor, etc., and is preferably less than 1 mm, for example. By doing so, it is possible to give sufficient compression and shearing forces to the mixture of raw material powders, and the reaction between the raw material powders can be promoted. The gap is preferably 0.9 mm or less, and more preferably 0.8 mm or less. The lower limit of the gap is, for example, 100 μm or more, and preferably 0.5 mm or more.

[0052] In addition, the power of the rotation of the rotor is, for example, 0.05 kW / g or more relative to the total mass of the raw material powders. By increasing the rotational power, the solid phase reaction between the raw material powders is promoted. The power of the rotation is preferably 0.06 kW / g or more, more preferably 0.08 kW / g or more, and particularly preferably 0.1 kW / g or more. The upper limit of the power of the rotation is not particularly limited, for example, 0.5 kW / g. The rotational speed of the rotor varies depending on the size of the device, the shape of the rotor, etc. For the rotational power in the above range, it is, for example, 2000 to 6000 rpm, preferably 3000 to 5000 rpm.

[0053] The rotation time of the rotor can be appropriately set according to the rotational power of the rotor, for example, more than 5 minutes, preferably more than 10 minutes, and more preferably more than 15 minutes. By rotating the rotor for more than 5 minutes (preferably more than 10 minutes), the compression force and shear force can be fully applied to the raw material powder, so the solid phase reaction of the raw material powder progresses and LLZ can be obtained. The upper limit of the rotation time of the rotor is not particularly limited. If it is too long, the crystallinity of LLZ will be reduced instead, and excess energy will be consumed. Therefore, it is preferably less than 40 minutes, and more preferably less than 30 minutes.

[0054] In the mechanochemical treatment, strain energy is accumulated in the raw material powder by shearing, and the energy is released by itself to become thermal energy, thereby generating heat. Therefore, the manufacturing method of the present invention can also be implemented in a state where heating based on an external heat source is not performed. The mechanochemical treatment can be performed in a state of heating, or by cooling by water cooling or the like. In the mechanochemical treatment, the reaching temperature of the cylindrical container can be set to, for example, 50°C or more, preferably 130°C or more, and can also be set to 500°C or less.

[0055] The atmosphere of the mechanochemical treatment is not particularly limited, and may be any of an oxygen-containing atmosphere such as air or an inert gas atmosphere. Examples of the inert gas include nitrogen, helium, and argon (particularly preferably nitrogen).

[0056] The material of the bottomed cylindrical container is not particularly limited, and examples thereof include stainless steel such as SUS304, carbon steel, etc. Alternatively, the generated LLZ may be coated so that impurities are not mixed in. The inner diameter of the container is, for example, 50 to 500 mm. In addition, the number of the front blades may be one or more, preferably two or more, and usually eight or less.

[0057] The raw material powders are Li source powder, La source powder, Zr source powder and Ga source powder. As Li source powder, La source powder, Zr source powder and Ga source powder, for example, oxides, carbonates, hydroxides, chlorides, alkoxides and the like of each metal (Li, La, Zr or Ga) can be used. The Li source powder is preferably Li oxide or Li carbonate, the La source powder is preferably La oxide or La hydroxide, the Zr source powder is preferably Zr oxide or Zr hydroxide, and the Ga source powder is preferably Ga oxide or Ga hydroxide. The Li source powder, La source powder, Zr source powder and Ga source powder are preferably oxides (Li oxide, La oxide, Zr oxide and Ga oxide) powders of each metal.

[0058] The ratio of Li source powder, La source powder, Zr source powder, and Ga source powder can be set to the stoichiometric ratio of the target composition. In particular, the amount of Ga relative to the amount of Li is preferably set to 0.02 or more in molar ratio, so that the crystal system of LLZ obtained by such operation can be cubic. The above molar ratio is more preferably 0.03 or more, further preferably 0.04 or more, further preferably 0.06 or more, and particularly preferably 0.08 or more, and the upper limit is not limited, for example, 0.2 or less.

[0059] It is also preferable to appropriately adjust the powder properties of each raw material powder, such as the specific surface area S based on the BET method. w (m 2 / g) is preferably 0.5 to 25 m 2 / g. In addition, the specific surface area S w , calculate the specific surface area diameter d by the following formula BET (nm).

[0060] d BET =6 / (ρ·S w )

[0061] (In the above formula, ρ represents the theoretical density)

[0062] For the preferred specific surface area diameter d BET In terms of (nm), the Li source powder is 250 to 400 nm, the La source powder is 30 to 150 nm, the Zr source powder is 20 to 100 nm, and the Ga source powder is 20 to 100 nm.

[0063] The aforementioned reaction aid includes LiX 1 With MX 2 p (X 1 and X 2 All are F, Cl, Br or I, X 1 and X 2are the same or different, M is Ba, Y, Sr, or Sc, and p is a value equal to the atomic valence of M). 1 and MX 2 p The total amount of LiX 1 The amount is preferably 40 mol% or more. 1 The ratio of Li + Ionic conductivity. LiX 1 The ratio is more preferably 50 mol % or more, further preferably 60 mol % or more, and the upper limit is, for example, 95 mol % or less, and may be 90 mol % or less.

[0064] X 1 and X 2 All are preferably F. M is preferably Ba or Sr. LiX 1 With MX 2 p The mixture is most preferably a mixture of LiF and BaF2 or a mixture of LiF and SrF2.

[0065] It is also preferred to appropriately adjust the BET specific surface area diameter of the compound contained in the reaction aid. For example, the specific surface area diameter d of BaF2 obtained from the BET specific surface area is BET For example, the specific surface area diameter d of LiF calculated from the BET specific surface area is 100 to 200 nm. BET For example, it is 550 to 700 nm.

[0066] The amount of the reaction aid is preferably 15 parts by mass or less, more preferably 12 parts by mass or less, and further preferably 10 parts by mass or less, relative to 100 parts by mass of the mixture of raw material powders including the aforementioned Li source powder, La source powder, Zr source powder, and Ga source powder, and may be 4 parts by mass or more. The step of adding the reaction aid is not particularly limited, and it is preferred to add the reaction aid to the mixture of the aforementioned raw material powders to start the mechanochemical treatment.

[0067] LLZ can be generated by the aforementioned mechanochemical treatment alone, but it is preferred to perform calcination after the mechanochemical treatment to further increase the Li + Ion conductivity. The calcination temperature is preferably 1100 to 1350°C, more preferably 1150 to 1300°C, and further preferably 1200 to 1300°C. In addition, the calcination time is preferably 10 to 30 hours, more preferably 12 to 27 hours, and further preferably 15 to 25 hours. It should be noted that calcination is also preferably performed after the mechanochemically treated mixture is formed.

[0068] The solid electrolyte of the present invention which can be manufactured by the above method can also be the following solid electrolyte, that is, a solid electrolyte comprising a garnet-type composite metal oxide phase (L), wherein the solid electrolyte is a solid electrolyte comprising LiX 1 and MX 2 p (X 1 and X 2 All are F, Cl, Br or I, X 1 and X 2 The phase (L) is synthesized by mechanochemical treatment of a raw material mixture containing Li source powder, La source powder, Zr source powder and Ga source powder in the presence of a reaction aid of a mixture of two or more different materials (optionally the same or different, M is Ba, Y, Sr, or Sc, and p is a value equal to the atomic valence of M), wherein the phase (L) contains Li, La, Zr and O, and Ga that replaces a portion of the Li site. The reaction aid may contain LiX 1 and MX 2 p The reaction aid is preferably LiX 1 and MX 2 p The reaction aid LiX 1 and MX 2 p The total amount is preferably 90% by mass or more, more preferably 95% by mass or more, and also preferably 100% by mass.

[0069] Preferably, by using the reaction aid, a phase (D) exists at least partially at the interface of the phase (L), wherein the phase (D) is a phase containing a compound including at least part of the constituent elements of the reaction aid and is different from the phase (L).

[0070] When the reaction aid comprises a mixture of LiF and BaF2, it is preferred that at least one of LiF and BaZrO3 is contained in the compound comprising at least a part of the constituent elements of the reaction aid. When the compound comprising at least a part of the constituent elements of the reaction aid comprises LiF, it is more preferred that phase (D) further comprises at least one of Al element and La element. In particular, the target chemical composition is Li 7-x Ga x / 3 La3Zr2O 12When using Li source powder, La source powder, Zr source powder, and Ga source powder in the manner of (0 < x ≤ 1.5, preferably 0.3 ≤ x ≤ 0.8), that is, when the reaction aid is a mixture of LiF and BaF2 (especially the molar ratio of LiF to BaF2 is 50:50 to 90:10, preferably 80:20 to 90:10), and the reaction aid is 8 to 10 parts by mass relative to 100 parts by mass of the mixture of raw material powders, the compound containing at least a part of the constituent elements of the aforementioned reaction aid preferably contains BaZrO3. When the target chemical composition is Li 7-x Ga x / 3 La3Zr2O 12 When using Li source powder, La source powder, Zr source powder, and Ga source powder in the manner of (0 < x ≤ 1, preferably 0.3 ≤ x ≤ 0.8), that is, when the reaction aid is a mixture of LiF and BaF2 (especially the molar ratio of LiF to BaF2 is 80:20 to 90:10), and the reaction aid is 8 to 10 parts by mass relative to 100 parts by mass of the mixture of raw material powders, and further firing is carried out at 1100 to 1350 °C for 10 to 30 hours after mechanochemical treatment, the compound containing at least a part of the constituent elements of the aforementioned reaction aid preferably contains LiF and BaZrO3.

[0071] When the reaction aid contains a mixture of LiF and YF3, the compound containing at least a part of the constituent elements of the aforementioned reaction aid is preferably YF3. Especially when the target chemical composition is Li 7-x Ga x / 3 La3Zr2O 12 When using Li source powder, La source powder, Zr source powder, and Ga source powder in the manner of (0 < x ≤ 1, preferably 0.3 ≤ x ≤ 0.8), that is, when the reaction aid is a mixture of LiF and YF3 (especially the molar ratio of LiF to YF3 is 80:20 to 90:10), and the reaction aid is 8 to 10 parts by mass relative to 100 parts by mass of the mixture of raw material powders, and further firing is carried out at 1100 to 1350 °C for 10 to 30 hours after mechanochemical treatment, the compound containing at least a part of the constituent elements of the aforementioned reaction aid preferably contains YF3.

[0072] When the reaction aid contains a mixture of LiF and SrF2, the compound containing at least a part of the constituent elements of the aforementioned reaction aid is preferably SrF2. Especially when the target chemical composition is Li 7-x Ga x / 3 La3Zr2O 12When using the Li source powder, La source powder, Zr source powder, and Ga source powder in the manner of (0 < x ≤ 1, preferably 0.3 ≤ x ≤ 0.8), that is, when the reaction aid is a mixture of LiF and SrF2 (especially the molar ratio of LiF to SrF2 is 80:20 to 90:10), and the reaction aid is 8 to 10 parts by mass relative to 100 parts by mass of the mixture of raw material powders, and then firing is carried out at 1100 to 1350 °C for 10 to 30 hours after mechanochemical treatment, the compound containing at least a part of the constituent elements of the aforementioned reaction aid preferably contains SrF2. In this case, it is preferable to contain SrF2 and Li2O simultaneously.

[0073] When the reaction aid contains a mixture of LiF and ScF3, the compound containing at least a part of the constituent elements of the aforementioned reaction aid is preferably ScF3. Especially when the target chemical composition is Li 7-x Ga x / 3 La3Zr2O 12 When using the Li source powder, La source powder, Zr source powder, and Ga source powder in the manner of (0 < x ≤ 1, preferably 0.3 ≤ x ≤ 0.8), that is, when the reaction aid is a mixture of LiF and ScF3 (especially the molar ratio of LiF to ScF3 is 80:20 to 90:10), and the reaction aid is 8 to 10 parts by mass relative to 100 parts by mass of the mixture of raw material powders, and then firing is carried out at 1100 to 1350 °C for 10 to 30 hours after mechanochemical treatment, the compound containing at least a part of the constituent elements of the aforementioned reaction aid preferably contains ScF3.

[0074] For the solid electrolyte of the present invention, the Li + ion conductivity at room temperature based on impedance measurement can be set to 1.0×10 -4 S / cm or more, preferably 1.5×10 -4 S / cm or more, more preferably 2.0×10 -4 S / cm or more. There is no limit to the upper limit, for example, it is 8.0×10 -4 S / cm or less. In addition, the activation energy Ea based on impedance measurement can be 0.4 eV or less, preferably 0.35 eV or less, more preferably 0.30 eV or less, and the lower limit can be 0.10 eV, for example. It should be noted that the aforementioned Li + ion conductivity can be measured by forming the solid electrolyte of the present invention into a shaped body having a relative density within the aforementioned preferred relative density range.

[0075] This application claims the benefit of priority based on Japanese Patent Application No. 2020-018115 filed on February 5, 2020. The entire contents of the specification of Japanese Patent Application No. 2020-018115 filed on February 5, 2020 are incorporated herein by reference.

[0076] Example

[0077] The present invention is not limited to the following examples, and can be implemented with appropriate modifications within the scope of the above and below-mentioned purposes, and all of them are included in the technical scope of the present invention.

[0078] Production Example 1-1

[0079] As Li 5.5 Ga 0.5 La3Zr2O 12 The raw materials are Li2O, La2O3, ZrO2, and Ga2O3 powders having the following characteristics, and the resulting composite metal oxides are Li 5.5 Ga 0.5 La3Zr2O 12 Weigh a total of 20g in the stoichiometric ratio.

[0080] Li2O: The following Li2O was used: manufactured by Kojundo Chemical Laboratory Co., Ltd., purity: 99%, specific surface area: S w : 2.1m 2 / g, specific surface area diameter d BET : 1421nm Li2O and 50cc of zirconia balls were added to a 100cc container made of zirconia and dry-pulverized at 96rpm for 24h (in the glove box: dew point value -90℃) to obtain the specific surface area S w :8.4m 2 / g, specific surface area diameter d BET : 355nm Li2O.

[0081] La2O3: The following La2O3 was used: 5 mm, 500 cc zirconia balls, ethanol, and La2O3 were placed in a 1 L container made of zirconia. The La2O3 was made by Kojundo Chemical Laboratory Co., Ltd., with a purity of 99.9% and a specific surface area of ​​S w : 1.7m 2 / g, specific surface area diameter d BET : 543 nm, the specific surface area S obtained by wet grinding at 80 rpm for 24 h in an air atmospherew : 11.5m 2 / g, specific surface area diameter d BET : 80nm La2O3.

[0082] ZrO2: manufactured by Kojundo Chemical Laboratory Co., Ltd., purity: 98%, specific surface area: S w :18.4m 2 / g, specific surface area diameter d BET : 57nm ZrO2.

[0083] Ga2O3: manufactured by Kojundo Chemical Laboratory Co., Ltd., purity: 99.99%, specific surface area: S w :10.4m 2 / g, specific surface area diameter d BET : 90nm Ga2O3.

[0084] Next, these raw materials and a mixture of LiF and BaF2 as a reaction aid (the molar ratio of LiF to BaF2 is 50:50, and the specific surface area diameter of LiF is d BET : 649nm, BaF2 specific surface area diameter d BET :137nm) invested in Figure 1 The amount of the reaction aid is 10 parts by mass relative to 100 parts by mass of the total amount of the raw materials. The bottomed cylindrical container 1 is made of SUS304 and has an inner diameter of 80 mm. The gap 4 between the inner circumference of the container 1 and the front blade 3 of the rotor 2 is set to 0.8 mm. Such a grinder is rotated in the atmosphere at a speed of 4500 rpm and a required power of 3 kW for 12 minutes to perform a mechanochemical treatment. It should be noted that the container has a reaching temperature of about 143.8°C.

[0085] Production Example 1-2

[0086] The mechanochemical treatment was carried out in the same manner as in Production Example 1-1 except that the reaction aid used was changed to a mixture of LiF and BaF 2 in which the molar ratio of LiF to BaF 2 was 75:25.

[0087] Production Example 1-3

[0088] The mechanochemical treatment was carried out in the same manner as in Production Example 1-1 except that the reaction aid used was changed to a mixture of LiF and BaF 2 in which the molar ratio of LiF to BaF 2 was 85:15 and the mill was rotated at 3 kW for 20 minutes.

[0089] Production Example 2-1

[0090] The powders of Li2O, La2O3, ZrO2 and Ga2O3 are respectively formed into Li 6.25 Ga 0.25 La3Zr2O 12 A total of 20 g was weighed in a stoichiometric ratio and the reaction aid used was changed to a mixture of LiF and BaF2 with a molar ratio of LiF to BaF2 of 85:15. The mechanochemical treatment was carried out in the same manner as in Production Example 1-1.

[0091] Production Example 2-2

[0092] The mechanochemical treatment was carried out in the same manner as in Production Example 2-1 except that the reaction aid used was changed to a mixture of LiF and BaF 2 in which the molar ratio of LiF to BaF 2 was 75:25.

[0093] Production Example 2-3

[0094] Mechanochemical treatment was performed in the same manner as in Production Example 2-1 except that the amount of the reaction aid added was 6 parts by mass based on 100 parts by mass of the total amount of the raw materials and the grinder was rotated at 3 kW for 17 minutes.

[0095] The results of analyzing the crystal structures of the samples obtained in Production Examples 1-1 to 1-3 using an XRD (X-ray Diffraction analysis) apparatus manufactured by Bruker are shown in FIG. Figure 2 The measurement was performed using CuKα rays, λ=1.5418nm, θ=10-50°. As a result, it was found that in the obtained sample, a cubic LLZ in which a part of the Li site was replaced by Ga was generated. In addition, the presence of BaZrO3 was also confirmed in Production Examples 1-1 to 1-3.

[0096] Similarly, the results of analyzing the crystal structures of the samples obtained in Production Examples 2-1 and 2-2 are shown in FIG. Figure 3 As a result, it was found that in the samples obtained in Production Examples 2-1 and 2-2, a cubic LLZ in which a part of the Li site was substituted with Ga was generated.

[0097] Production Example 3-1

[0098] The powders of Li2O, La2O3, ZrO2 and Ga2O3 are respectively formed into Li 6.4 Ga 0.2 La3Zr2O 12The total weight was 20 g, and the reaction aid used was changed to a mixture of LiF and YF3 with a molar ratio of LiF to YF3 of 75:25 (the specific surface area diameter d BET : 649 nm. The same is true for LiF used below. ) The mechanochemical treatment was performed in the same manner as in Production Example 1-1 except that the grinder was rotated at 3 kW for 39 minutes.

[0099] Production Example 3-2

[0100] The mechanochemical treatment was carried out in the same manner as in Production Example 3-1 except that the reaction aid used was changed to a mixture of LiF and YF3 in which the molar ratio of LiF to YF3 was 85:15 and the mill was rotated at 3 kW for 40 minutes.

[0101] Production Example 4-1

[0102] The powders of Li2O, La2O3, ZrO2 and Ga2O3 are respectively prepared into Li 6.4 Ga 0.2 La3Zr2O 12 A total of 20 g was weighed in a stoichiometric ratio, and the reaction aid used was changed to a mixture of LiF and SrF2 with a molar ratio of LiF to SrF2 of 85:15. The mechanochemical treatment was carried out in the same manner as in Production Example 1-1.

[0103] Production Example 5-1

[0104] The powders of Li2O, La2O3, ZrO2 and Ga2O3 are respectively prepared into Li 6.55 Ga 0.15 La3Zr2O 12 A total of 20 g was weighed in a stoichiometric ratio, and the reaction aid used was changed to a mixture of LiF and ScF3 with a molar ratio of LiF to ScF3 of 85:15, and the grinder was rotated at 3 kW for 30 minutes. Otherwise, the mechanochemical treatment was carried out in the same manner as in Manufacturing Example 1-1.

[0105] Examples 1-1 to 1-3, Examples 2-1 to 2-3, Examples 3-1 to 3-2, Examples 4-1 to 4-2, Example 5-1

[0106] The sample obtained in the above manufacturing example is placed in a mold and a pressure of 375 MPa is applied to form pellets with a diameter of 10 mm and a thickness of about 1 mm. The bottom of an alumina crucible is covered with tetragonal LLZO powder to suppress the volatilization of Li during sintering, and the formed pellets are allowed to stand on the covered LLZO powder. The pellets are then covered with LLZO powder and sintered at 1230°C for 20 hours in a dry nitrogen atmosphere to obtain a pellet sintered body. The weight of the pellet sintered body is measured, and the density is calculated based on the size of the pellets and the above weight, which is divided by the theoretical density of LLZ, which is 5.11 g / cm 3 Thus, the relative density (%) is calculated. Then, the two sides of the sintered pellets are ground and Au is sputtered in a drying room with a dew point of -60°C to form electrodes with a diameter of 8 mm. It should be noted that in Example 4-2, the pellets are formed and sintered as described above after the sample after the mechanochemical treatment is pulverized, thereby increasing the relative density. In addition, the pellet sintered body sample with the electrode formed is installed in a full solid-state battery evaluation battery cell manufactured by Hohsen Co., Ltd., connected to a potentiostat / galvanostat, and impedance measurements are performed in the temperature range of room temperature to 100°C to perform Li + Evaluation of ion conductivity (S / cm). Furthermore, activation energy E was calculated from the Arrhenius plot using the ion conductivity values ​​at each temperature. a (eV).

[0107] The pelletized sintered body was crushed in a glove box using a mortar, and the crystal structure was analyzed using a Bruker XRD (X-ray Diffraction analysis) device. The lattice constant was calculated by using the (400) peak of the obtained X-ray diffraction peak of LLZO and the interplanar spacing d value was calculated using the following formula.

[0108] 2dSinθ=nλ (1)

[0109] 1 / d 2 =(h 2 +k 2 +l 2 ) / a 2 (2)

[0110] d: interplanar spacing, a: lattice constant

[0111] The results are shown in Table 1.

[0112] [Table 1]

[0113]

[0114] According to Table 1, any embodiment shows 1.0×10-4 Good Li above S / cm + In addition, it can be seen that as the ratio of LiF increases, Li + The ion conductivity is improved.

[0115] In addition, for Example 2-1, a photograph in lieu of a drawing showing an image obtained by observing a cross section of a pellet using a TEM (transmission electron microscope, magnification 10,000 times) is shown in FIG. Figure 4 , Figure 5 . Figure 4 (a) is the SE (secondary electron) detector image. Figure 4 (b) is the ESB detector (Energy selected backscatter detector, Energy selected backscatter detector) image (composition image). Figure 4 , Figure 5 A phase clearly different from the LLZ was observed near the center of the portion surrounded by the dotted line.

[0116] Figure 6 This is a diagram showing the results of EDS analysis of the pellet cross section for Example 2-1. Near the LLZ particle interface, a site where La, Zr and Ba exist, a site where Ba and Zr exist, and a site where Al exist are observed. In the XRD analysis results of Example 2-1 described later, BaZrO3 is detected, and it is believed that the site where Ba and Zr exist is BaZrO3.

[0117] Figure 7 This is a diagram showing the results of TEM-EDS (Energy dispersive X-ray spectrometry) analysis of the cross section of Example 2-1. Figure 7 A phase containing La was observed at the interface of the LLZ phase, and Al was also detected in the phase containing La.

[0118] and then, Figure 8 for Figure 7 TEM-EELS images of position (I) and position (II). Figure 8 In the figure, the presence of LiF was confirmed in the central part of the EELS image at positions (I) and (II) (the bright part in the central part of the EELS image), and the presence of LiF was confirmed in a phase different from the LLZ phase at the interface of the LLZ phase.

[0119] Fig. 9This is the result of analyzing the crystal structure of the samples obtained in Manufacturing Example 2-1 and Example 2-1 using a Bruker XRD (X-ray Diffraction analysis) device. In Example 2-1, which was further calcined on Manufacturing Example 2-1, the half-value width of the peak corresponding to LLZ became smaller, and it can be seen that the crystallinity was improved by calcining. In addition, the presence of BaZrO3 can be confirmed in both Manufacturing Example 2-1 and Example 2-1.

[0120] Fig.10 The crystal structures of the samples obtained in Manufacturing Example 3-2 and Example 3-2 were analyzed using a Bruker XRD (X-ray Diffraction analysis) device. In Example 3-2, which was further calcined on Manufacturing Example 3-2, the half-value width of the peak corresponding to LLZ became smaller, indicating that the crystallinity was improved by calcination.

[0121] Fig.11 This is a diagram showing the results of EDS analysis of the pellet cross section in Example 3-2. The presence of Y and F was confirmed, and Y and F were observed at the same position at the LLZ interface, which suggests that YF3 was formed.

[0122] Fig.12 The crystal structures of the samples obtained in Manufacturing Example 4-1 and Example 4-1 were analyzed using a Bruker XRD (X-ray Diffraction analysis) device. In Example 4-1, which was further calcined on Manufacturing Example 4-1, the half-value width of the peak corresponding to LLZ became smaller, and it can be seen that the crystallinity was improved by calcination. In addition, the presence of Li2O can also be confirmed in Example 4-1.

[0123] Fig.13 This is a diagram showing the results of EDS analysis of the pellet cross section for Example 4-1. The presence of Sr and F was confirmed, and Sr and F were observed at the same position of the LLZ interface, and it is believed that SrF2 was formed. In addition, no other elements were observed at the position where O was observed. In addition, Li is a light element and its presence is difficult to confirm in EDS analysis. Fig.12 Considering the results together, it is believed that Li2O exists in part of the positions where O exists.

[0124] Fig.14The crystal structure of the sample obtained in the manufacturing example 5-1 and the embodiment 5-1 was analyzed using the XRD (X-ray Diffraction analysis) device made by Bruker. As for the embodiment 5-1 which further implemented the calcination of the manufacturing example 5-1, the half-value width of the peak corresponding to LLZ became smaller, and it can be known that the crystallinity was improved by calcination. In addition, the presence of ScF3 can also be confirmed in the embodiment 5-1.

[0125] Description of Reference Numerals

[0126] 1 Cylindrical container with bottom

[0127] 2 Rotors

[0128] 3 Front blade

[0129] 4 Clearance

[0130] 5. Mixture of raw material powder and reaction aid

Claims

1. A solid electrolyte, characterized in that: It contains a garnet-type composite metal oxide phase L and a phase D different from the phase L, The solid electrolyte is a LiX 1 and MX 2 p The raw material mixture containing Li source powder, La source powder, Zr source powder and Ga source powder is synthesized by mechanochemical treatment in the presence of a reaction aid of a mixture of 1 and X 2 are all F, M is Ba, Y, Sr, or Sc, and p is a value equal to the atomic valence of M. The LiX in the reaction aid 1 and MX 2 p The total amount is 90 mass % or more, relative to LiX 1 and MX 2 p The total amount of LiX 1 The amount is 50 mol% or more, and the amount of the reaction aid is 15 parts by mass or less relative to 100 parts by mass of the total raw material mixture, The phase L contains Li, La, Zr, and O, and Ga that replaces a portion of the Li site. The lattice constant of the solid electrolyte is greater than 12.96 Å, The phase D contains LiF and at least one selected from the group consisting of BaZrO 3 , YF 3 , SrF 2 , and ScF 3 .

2. The solid electrolyte according to claim 1, wherein The phase D further contains at least one of an Al element and a La element.

3. The solid electrolyte according to claim 1 or 2, wherein Phase D exists at least in a portion of the interface of phase L.

4. The solid electrolyte according to claim 1 or 2, wherein Li + The ionic conductivity is 1.0×10 -4 S / cm or more.

5. The solid electrolyte according to claim 1 or 2, wherein After the mechanochemical treatment, sintering is performed at 1100-1350° C. for 10-30 hours.

Citation Information

Patent Citations

  • Ion conductor, lithium battery, and method of producing ion conductor

    JP2017091788A

  • Motor and ducted fan

    JP2020018115A

  • Fluorine-containing garnet-structure lithium ion oxide ceramic

    CN104591231A

  • Lithium-lanthanum-zirconium oxide-based solid electrolyte material capable of inhibiting lithium dendrites, and preparation method and application thereof

    CN110176627A

  • Ceramic powder, sintered body and battery

    WO2019189275A1